Evaluating the Impact of Lenalidomide on Bone Marrow Cancer Treatment: Monitoring White Blood Cell, Hemoglobin, and Platelet Levels - Hiba Jumaa Hussein; Lara Ali Nazar; Hamsa Ghwamer Ghazi (Journal of Applied Hematology)
BACKGROUND: Lenalidomide (LEN), also known as Revlimid, is a drug used to treat multiple myeloma (MM), smoldering myeloma, and myelodysplastic syndromes. It is used as a first-line treatment for MM, along with dexamethasone. OBJECTIVE: To investigate the effects of LEN on the function of bone marrow (BM) by monitoring the changes in the number of white blood cells (WBCs), hemoglobin levels, and platelet counts in people who were getting treatment. MATERIALS AND METHODS: Includes 90 blood samples from 30 cancer patients before treatment and 30 cancer patients after treatment and 30 healthy individuals aged 60–75 years and is conducted at City Medical Hospital. The blood samples are analyzed to detect Erythrocyte Sedimentation Rate (ESR) by using an ESR fast detector, and detect WBC, red blood cell, and platelets by Mindray CBC-21S. Tests are performed weekly initially, and then biweekly or monthly, taking into account ethical issues such as obtaining consent and criteria for adjusting treatment based on side effects or changes in blood counts. RESULTS: The findings revealed a notable change in the amount of WBCs at the start of the study. These cells significantly decreased and then level off a few months after treatment (2–5) months. Before and after medication, the levels of hemoglobin were changing. The results also showed that the number of platelets in some cases dropped by a large amount. CONCLUSION: Adding LEN could help patients with BM cancer since it reduces microvascularization and most likely increases the particular T cell-driven anti-leukemic response.